Computer-Assisted Text Analysis for Comparative Politics. (2015) - Lucas, Christopher; Nielsen, Richard A.; Roberts, Margaret E.; Stewart, Brandon M.; Storer, Alex; Tingley, Dustin
Abstract : Recent advances in research tools for the systematic analysis of textual data are enabling exciting new research throughout the social sciences. For comparative politics, scholars who are often interested in non-English and possibly multilingual textual datasets, these advances may be difficult to access. This article discusses practical issues that arise in the processing, management, translation, and analysis of textual data with a particular focus on how procedures differ across languages. These procedures are combined in two applied examples of automated text analysis using the recently introduced Structural Topic Model. We also show how the model can be used to analyze data that have been translated into a single language via machine translation tools. All the methods we describe here are implemented in open-source software packages available from the authors.